IMPLEMENTASI PROGRAM PENCEGAHAN PERKAWINAN PADA USIA ANAK DI KABUPATEN BOJONEGORO (STUDI KASUS KECAMATAN KAPAS) - Heny Suhindarno; Mochtar Setjohadi (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This research aims to determine the implementation of the early marriage prevention program in Bone Regency and to identify the supporting and inhibiting factors in the prevention of child marriage in Bojonegoro Regency. The prevention of child marriage is useful to minimize incidents or actions carried out by young couples under the age of 19. The type of research used is qualitative research with a descriptive approach, in which the data were obtained through observation, interviews, and documentation. The informants in this study amounted to 11 people, consisting of 1 Head of the P3AKB Office, 1 PLKB Coordinator, 2 Task Force Cadres, 2 adolescents who married at a child age, and 2 adolescents who have not yet married. The results of the study show that the minimum age for marriage has been stipulated in Article 7 paragraph (1) of Law No. 16 of 2019; however, in practice, there are still many child marriages occurring in Bojonegoro Regency. Some adolescents agree with the program because it is considered to safeguard the future of young people, while others do not fully agree with the program because there are certain aspects that need to be considered once the matter has entered into legal proceedings.